Fish Community Structure in Seagrass Beds of Doreri Bay Manokwari Regency - Wilhelmus Reinaldo Pattipeilohy; Thomas Frans Pattiasina; Simon Petrus Octavianus Leatemia; Selfanie Talakua (Faculty of Agriculture Musamus University, 2020)
One of the coastal ecosystems that has a high primary productivity, seagrass, makes it a places to find foods (feeding ground), spawn (spawning ground), and shelter for most fish. Whether the structure of fish communities on seagrass beds in the coastal waters of Doreri Bay based on day and night observation times is different from previous studies. This study aims to examine the structure of fish communities on seagrass beds in the coastal waters of Doreri Bay, between the time of observation and compared to previous studies. Data collection takes place during April-May 2019. The method used in this study is a descriptive method, using 1 and 1.5 inch gills net. The results of the study found that seagrass beds in Doreri Bay waters were more than in previous studies, which consisted of 10 species of seagrasses from 2 families (Hydrocharitaceae and Cymodoceaceae). The composition of fish is 56 species with a total of 91 individuals during the day and 189 individuals at night. Fish community structure in Doreri Bay waters has moderate diversity and uniformity while low dominance. Efforts should be made to protect seagrass ecosystems so that fish resources in the Doreri Bay region are maintained.